The Third Cohesion Report and the European Spatial Development Perspective - Andreas Faludi (European Journal of Spatial Development, 2004)
The third Cohesion Report has been keenly awaited. Does it open up new perspectives on the continuation, albeit under the flag of territorial cohesion policy, of the ESDP process, important also for the future of ESPON, in which so many researchers on European spatial development are presently engaged? After all, ESPON was set up to prepare us for the next ESDP!